Targeted Molecular Design of Functionalized Fullerenes for High‐Performance and Stable Perovskite Solar Cells. Issue 6 (15th April 2022) - Xing, Zhou; Li, Shu-Hui; Yang, Shihe
Abstract : Perovskite solar cell (PSC) is a potential next‐generation photovoltaic technology alternative to the conventional competitors including polycrystalline silicon, cadmium telluride, and copper indium gallium diselenide solar cells. Particularly, functionalized fullerenes play crucial roles as charge transport layers, interfacial layers, and additives in perovskite photovoltaics, dramatically contributing to the promotion of power conversion efficiency (PCE) and stability. As the field advances rapidly, the importance to rationally design fullerenes against a particular category of those functions has been increasingly recognized. Herein, recent progress in the application of functionalized fullerenes toward high‐performance and stable perovskite solar cells is reviewed, placing special emphasis on the importance of the targeted molecular design of fullerene structures for different application scenarios to meet diverse functional requirements in specific device structures. Abstract : Functionalized fullerenes promote the development of high‐performance and stable perovskite solar cells (PSCs) by acting as electron/hole transport layers, interfacial layers, and additives. Four issues should be considered when designing functionalized fullerenes, including solubility (soluble group, solvent, addition mode), electronic property (intermolecular interaction, packing mode), intrinsic stability (photo‐/thermo‐stability), and multi‐functionalization (bridging agent, passivant, stability enhancer).